2016
DOI: 10.3906/sag-1410-95
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of mean platelet volume with retinopathy in type 2 diabetes mellitus

Abstract: IntroductionDiabetes mellitus (DM), a major global health problem, is commonly associated with increased risk of developing micro-and macrovascular disease. Despite its clinical importance, the pathophysiology of diabetic complications is not completely understood. Platelets have been thought to be involved in these complications. Diabetic retinopathy (DR) is one of those important complications and leads to a considerable increase in morbidity.Platelet volume is a marker of platelet activation and function th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…Our study suggests that increased MPV is associated with poor glycemic control. This coincides with the results of Kodiatte et al, 4 Rajesh Kanna, 5 Jindal et al, 10 Buch et al, 11 Hasan et al, 17 Zaccardi et al, 18 Vernekar et al, 19 Shah b et al, 20 Zuberi et al, 21 Ozder et al, 24 Dindar et al, 26 Papanas et al, 27 Gungor et al, 28 Hekimsoy et al 30 Demirtunc et al 33 and Coban et al 35 but contradicts the results of Dayal et al, 2 Cakir et al, 31 Unübol et al 36 and Alhadas et al 22 found a positive correlation between both MPV and PDW and blood glucose levels.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study suggests that increased MPV is associated with poor glycemic control. This coincides with the results of Kodiatte et al, 4 Rajesh Kanna, 5 Jindal et al, 10 Buch et al, 11 Hasan et al, 17 Zaccardi et al, 18 Vernekar et al, 19 Shah b et al, 20 Zuberi et al, 21 Ozder et al, 24 Dindar et al, 26 Papanas et al, 27 Gungor et al, 28 Hekimsoy et al 30 Demirtunc et al 33 and Coban et al 35 but contradicts the results of Dayal et al, 2 Cakir et al, 31 Unübol et al 36 and Alhadas et al 22 found a positive correlation between both MPV and PDW and blood glucose levels.…”
Section: Discussionsupporting
confidence: 86%
“…In our study no correlation was found between MPV and PDW, and duration of diabetes similar to Papanas et al, 27 Madhavan et al, 23 Cakir et al 31 and Hasan et al 37 However Kodiette et al, 4 Akinsegun et al 13 and Gungor et al 28 found significant correlation between MPV and duration of diabetes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A sample size of 146 was calculated using frequency of MPV in patients with type 2 diabetes with WHO sample size calculator considering 5% level of significance, and 95% confidence interval. Sampling technique used was non-probability consecutive sampling 10 . All adult patients who were diagnosed cases of diabetes as per American Diabetic Association (ADA) irrespective of their gender, socio-economic status, duration of the disease and age above 25 years were included in this study.…”
Section: Introductionmentioning
confidence: 99%